Analisis Citraan dalam Light Novel Classroom of the Elite Volume 7.5 Karya Shogo Kinugasa: Pendekatan Stilistika - Adam, Daniel; Riadi, Selamet; Fahmi, Farizan (Tirai Edukasi : Jurnal Pendidikan, 2023)
This study analyzes the use of imagery in Shogo Kinugasa's light novel Classroom of the Elite (COTE) Volume 7.5 through a stylistic approach. The research aims to identify types of imagery based on Nurgiyantoro's (2017) theory and examine their impact on stimulating readers' sensory perception. A descriptive qualitative method was employed, with data collected via documentation and literature study. A total of 727 text excerpts were classified into five imagery types: visual (338 instances), auditory (259 instances), kinesthetic (211 instances), tactile (20 instances), and olfactory (1 instance). Findings reveal that visual and kinesthetic imagery dominate the narrative, while auditory imagery critically constructs psychological atmosphere. Tactile and olfactory imagery enrich relational intimacy. The study concludes that imagery functions as a narrative instrument that strengthens characterization, psychological tension, and readers' sensory experiences.